PENGARUH PENGETAHUAN MENGENAI RISIKO DAN KOMPETENSI TERHADAP KINERJA UNDERWRITER PERUSAHAAN DI INDUSTRI ASURANSI KERUGIAN (UMUM) DI INDONESIA - Mohammad Subhan (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: The objective of this study was to determine whether Knowledge about the risk and Competence affect the Undewriter performance of companies in General Insurance Industry in Indonesia. Respondents in this study is the Head of Underwriting or Head of Marine Underwriting Section and Head of Non-Marine Underwriting Section or the representative, of the total sample of 68 companies in the GeneralInsurance Industry in Indonesia. From this study, the results showed that Knowledge about the risks and Competence has a positive relationship either partially or simultaneously with The Underwriters performance, so Knowledge about the risks and Competence significant effect on The Underwriter Performance, either partially or simultaneously anyway.Keywords: Knowledge about risk, Competence, Performance Underwriter